(untitled) (Annals of Medical Research, 2021)
Aim: To evaluate the relationship between scleral and conjunctival thickness with age in normal subjectsMaterial and Methods: One hundred five normal subjects were evaluated in this study. Scleral thickness (ST) and conjunctival thickness( CT) were measured by Spectralis Anterior Segment Module Optical Coherence Tomography (AS-OCT). ST and CT were measured at a distance of 1,000, 2,000, 3,000, 4,000 and 5,000 microns from temporal scleral spur. The mean sclera (STmean) and conjunctival (CTmean) thickness were obtained by the mean of the sclera and conjunctival thickness at 5 points. The axial length (AL) was evaluated by using AL-Scan Optical Biometer(Nidek co.,ltd.). SPSS 21 was used for statistical analysis. Results: There was no significant difference between males and females according to ST, CT and AL values (p>0.05). There was a significant positive correlation between age and ST values at 2000, 3000, 4000, and 5000 micron apart from temporal scleral spur (r=0.237 p=0.015, r=0.241 p=0.013, r=0.276 p=0.004, r=0.202 p=0.039 respectively). There was a significant negative correlation between age and CT values at 3000, 4000 and, 5000 micron apart from temporal scleral spur(r= -0.222 p=0.023, r= -0.288 p=0.003,r= -0.350 p0.001). There was a significant positive correlation between age and STmean and, a negative between age and CTmean (r=0.289 p=0.003, r= -0.251 p=0.010) .Conclusion: According to this study ST positively and CT negatively correlated with age significantly.